(untitled) (E-Journal of Cultural Studies, 2026)
This article examines how cultural experiences are created and negotiated within the landscape of creative tourism in Ubud, using Balinese dance classes as a case study. Creative tourism is not only a space for the exchange of cultural knowledge and skills between tourists and local communities, but also a field where cultural capital, economic interests, and power relations continuously shape the production and perception of Balinese culture. In this study, Balinese dance classes are understood as a performative field in which "Balineseness" is simplified and negotiated. This research employs an ethnographic method, involving semi-structured interviews, participant observation, and document analysis. The findings show that creative tourism remains an opportunity for local communities to gain economic benefits from their cultural expertise. However, the scale and sustainability of these benefits are strongly influenced by economic capital, language skills, social networks, and symbolic legitimacy. The challenges of cultural commodification are interpreted differently by local actors as part of the realities of tourism practices in Bali.